19. Performing Iannis Xenakis’s Polyrhythms: A Perception-informed Approach to Renotation - Imri Talgam (Meta-Xenakis: New Perspectives on Iannis Xenakis’s Life, Work, and Legacies, 2024)
Xenakis often uses complex superimposed polyrhythms that are uniquely challenging for performers to realize, especially in solo and chamber works. Faced with overwhelming rhythmic complexity, performers must choose a strategy to navigate the score, often resulting in informal compromises and approximations. As an alternative, in this chapter, I propose a methodological approach to performance of rhythmic complexity using re-notation informed by theories of metric perception. Using examples from Mists, À l’île de Gorée, and Dikhthas, I identify three classes of rhythmic textures: irregular a-metrical rhythms, isochronous polyrhythms, and phase-shifted polyrhythms. While Xenakis’s notation clearly conveys these distinct ideas, it does not facilitate accurate realization in performance, which diminishes the polyphonic quality of these passages. My methodology proceeds in several stages: a) Analysis of the primary cues for grouping and possible metric interpretations of each rhythmic texture using the theory proposed by London; b) using the notion of context-sensitive constraints on metric perception (I propose a quantization strategy to reduce the complexity of the rhythm while preserving the macro characteristics; c) proposal of several possible re-notations, depending on the grouping cues or pulse layers that are taken as the tactus in the passage, while relegating other layers to ana-metrical status. Since multiple versions may be beneficial in representing different aspect of the music, I consider their advantages from both performers’ and listeners’ perspectives; d) finally, I examine the dynamics of listening and synchronization between multiple players in realizing rhythmically complex passages, in which players create a metric interpretation collaboratively.